Gentian FLOWERING LOCUS T orthologs regulate phase transitions: floral induction and endodormancy release. Issue 4 (13th January 2022) - Takahashi, Hideyuki; Nishihara, Masahiro; Yoshida, Chiharu; Itoh, Kimiko
Abstract: Perennial plants undergo a dormant period in addition to the growth and flowering phases that are commonly observed in annuals and perennials. Consequently, the regulation of these phase transitions in perennials is believed to be complicated. Previous studies have proposed that orthologs of FLOWERING LOCUS T ( FT ) regulate not only floral initiation but also dormancy. We, therefore, investigated the involvement of FT orthologs ( GtFT1 and GtFT2 ) during the phase transitions of the herbaceous perennial gentian ( Gentiana triflora ). Analysis of seasonal fluctuations in the expression of these genes revealed that GtFT1 expression increased prior to budbreak and flowering, whereas GtFT2 expression was induced by chilling temperatures with the highest expression occurring when endodormancy was released. The expression of FT -related transcription factors, reportedly involved in flowering, also fluctuated during each phase transition. These results suggested the involvement of GtFT1 in budbreak and floral induction and GtFT2 in dormancy regulation, implying that the two gentian FT orthologs activated a different set of transcription factors. Gentian ft2 mutants generated by CRISPR/Cas9-mediated genome editing had a lower frequency of budbreak and budbreak delay in overwintering buds caused by an incomplete endodormancy release. Our results highlighted that the gentian orthologs of FRUITFULL ( GtFUL ) and SHORT VEGETATIVE PHASE-like 1 ( GtSVP-L1 ) act downstream of GtFT2, probably to prevent untimely budbreak during ecodormancy. These results suggest that each gentian FT ortholog regulates a different phase transition by having variable responses to endogenous or environmental cues, leading to their ability to induce the expression of distinct downstream genes. Abstract : Gentian FLOWERING LOCUS T orthologs have diverse functions: GtFT1 promotes flowering, and GtFT2 promotes bud endodormancy release and functions with FRUITFULL to prevent untimely budbreak.